1999
DOI: 10.1128/jcm.37.9.2750-2754.1999
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Rhinosporidium seeberi ’s 18S Small-Subunit Ribosomal DNA Groups This Pathogen among Members of the Protoctistan Mesomycetozoa Clade

Abstract: For the past 100 years the phylogenetic affinities ofRhinosporidium seeberi have been controversial. Based on its morphological features, it has been classified as a protozoan or as a member of the kingdom Fungi. We have amplified and sequenced nearly a full-length 18S small-subunit (SSU) ribosomal DNA (rDNA) sequence fromR. seeberi. Using phylogenetic analysis, by parsimony and distance methods, of R. seeberi’s 18S SSU rDNA and that of other eukaryotes, we found that this enigmatic pathogen of humans and anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(102 citation statements)
references
References 22 publications
7
90
0
2
Order By: Relevance
“…Nasal disease may rarely be caused by Rhinosporidium seeberi, an aquatic protistan parasite of the Mesomycetozoa family, which some refer to as the DRIP (Dermocystidium, the "rosette agent," Ichthyophonus, Psorospermium) clade. 17,18 Development of mature endospores is stimulated by water exposure, therefore this agent is associated with wet environments. 19 The parasite is endemic in India, Sri Lanka, and Argentina 19 and sporadic cases have been reported in Canada, 20 the United Kingdom, 21 Italy, 22 and the United States.…”
Section: Rhinosporidiosismentioning
confidence: 99%
“…Nasal disease may rarely be caused by Rhinosporidium seeberi, an aquatic protistan parasite of the Mesomycetozoa family, which some refer to as the DRIP (Dermocystidium, the "rosette agent," Ichthyophonus, Psorospermium) clade. 17,18 Development of mature endospores is stimulated by water exposure, therefore this agent is associated with wet environments. 19 The parasite is endemic in India, Sri Lanka, and Argentina 19 and sporadic cases have been reported in Canada, 20 the United Kingdom, 21 Italy, 22 and the United States.…”
Section: Rhinosporidiosismentioning
confidence: 99%
“…Arseculeratne 5 found no evidence of any relationship between M. aeruginosa and R. seeberi. In recent molecular studies, Herr et al 1 suggested that R. seeberi is a protist belonging to a novel group of fish parasites, Mesomycetozoa, which is located phylogenetically between fungal and animal divergence. The protistan nature of this organism was also confirmed by other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, Rhinosporidium seeberi (R. seeberi) the causative agent, was categorized as a fungus, but newer findings reveal R. seeberi as a protist belonging to a novel group of fish parasites. 1 Although cases of Rhinosporidiosis have been reported worldwide, it is endemic in South Asia, with the highest incidence in India and Sri Lanka. The four common forms of Rhinosporidiosis are nasal, ocular, cutaneous, and disseminated; however, cases have been reported in the ear, trachea, larynx, brain, urethra, vulva, vagina, and parotid duct.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that R. seeberi is not a fungus but a protist belonging to a novel group identified as Mesomycetozoa, which is located phylogenetically between the fungal and animal divergence. 3 The mode of transmission of rhinosporidiosis is yet to be demonstrated definitively. The spores probably from animal sources infect humans through air and water.…”
Section: Discussionmentioning
confidence: 99%